Rights to Education for Poor Peoples: How The Country Protect Them? - Luthfi Widyantoko (The Indonesian Journal of International Clinical Legal Education, 2020)
This paper discusses the rights of the poor and marginalized in obtaining the right to education as one of the basic human rights. This paper is based on the condition that the urgency of educational development is one of the top priorities in the national development agenda. Educational development is very important because of its significant role in achieving progress in various fields of life: social, economic, political, and cultural. Therefore, the Government is obliged to fulfill the rights of every citizen in obtaining education services in order to improve the quality of life of the Indonesian people as mandated by the 1945 Constitution, which requires the Government to be responsible in educating the life of the nation and creating public welfare. The lack of equal distribution of education in Indonesia is a classic problem which until now there has not been any strategic steps from the government to handle it. This paper confirms that the achievement of the right to education in Indonesia has not been achieved and is motivated by several key factors, among government policies. In addition, human resources and infrastructure are also one of the causes of unequal access to education in Indonesia.